Fatty liver index is a predictor of incident diabetes in patients with prediabetes: The PREDAPS study. - Josep Franch-Nadal; Llorenç Caballeria; Manel Mata-Cases; Didac Mauricio; Carolina Giraldez-García; José Mancera; Albert Goday; Xavier Mundet-Tudurí; Enrique Regidor; PREDAPS Study Group (PLoS ONE, 2018)
OBJECTIVES:We evaluated the ability of the Fatty Liver Index (FLI), a surrogate marker of hepatic steatosis, to predict the development of type 2 diabetes (T2D) at 3 years follow-up in a Spanish cohort with prediabetes from a prospective observational study in primary care (PREDAPS). METHODS:FLI was calculated at baseline for 1,142 adult subjects with prediabetes attending primary care centers, and classified into three categories: FLI <30 (no steatosis), FLI 30-60 (intermediate) and FLI ≥60 (hepatic steatosis). We estimated the incidence rate of T2D in each FLI category at 3 years of follow-up. The association between FLI and incident T2D was calculated using Cox regression models adjusted for age, sex, educational level, family history of diabetes, lifestyles, hypertension, lipid profile and transaminases. RESULTS:The proportion of subjects with prediabetes and hepatic steatosis (FLI ≥60) at baseline was 55.7%. The incidence rate of T2D at 3 years follow-up was 1.3, 2.9 and 6.0 per 100 person-years for FLI<30, FLI 30->60 and FLI ≥60, respectively. The most significant variables increasing the risk of developing T2D were metabolic syndrome (hazard ratio [HR] = 3.02; 95% confidence interval [CI] = 2.14-4.26) and FLI ≥60 (HR = 4.52; 95%CI = 2.10-9.72). Moreover, FLI ≥60 was independently associated with T2D incidence: the HR was 4.97 (95% CI: 2.28-10.80) in the base regression model adjusted by sex, age and educational level, and 3.21 (95%CI: 1.45-7.09) in the fully adjusted model. CONCLUSIONS:FLI may be considered an easy and valuable early indicator of high risk of incident T2D in patients with prediabetes attended in primary care, which could allow the adoption of effective measures needed to prevent and reduce the progression of the disease.